Teachers’ creativity in designing English teaching learning material by Prajabatan student Program Profesi Guru (PPG) batch II - Sintia Friskila Rajagukguk; Kammer Tuahman Sipayung; Arsen Nahum Pasaribu; Erika Sinambela (Inovasi Kurikulum, 2024)
This research aimed to describe the teachers’ ways of designing creative English teaching learning material and to understand the factors of designing creative teaching material. The subjects of this study were ten Pra-Service Teacher Professional Education (PPG). This study used a descriptive qualitative research design. The data used to analyze were the transcripts of video learning and interviews. In the data analysis, it is found that there were seven aspects in designing their creative English learning material: 1) using an eclectic choice of method, 2) using activities that have creative dimensions, 3) teaching in a flexible way or adjusting and modifying the teaching during lessons, 4) looking for new ways of doing something, 5) adapting lessons, 6) using technology, and 7) looking for creative ways to motivate students. As a result, all the teachers apply those seven aspects during their teaching-learning process. There were three factors why English teachers design creative English teaching learning material: 1) the learning material is contextualized, 2) the learning material is designed for students' needs, and 3) personalization. After analyzing the data, it could be decided that all teachers have those three factors in designing their creative English learning material. Pre-service teacher Professional Education (PPG) was quite creative in designing teaching-learning materials. AbstrakPenelitian ini bertujuan untuk mendeskripsikan cara guru merancang bahan ajar bahasa Inggris yang kreatif dan untuk memahami faktor-faktor dalam merancang bahan ajar yang kreatif. Subyek penelitian ini adalah sepuluh Prajabatan Pendidikan Profesi Guru (PPG), Penelitian ini menggunakan desain penelitian deskriptif kualitatif, Data yang digunakan untuk menganalisis adalah transkrip video pembelajaran dan transkrip wawancara. Dalam analisis data ditemukan tujuh aspek dalam merancang materi pembelajaran bahasa Inggris kreatif mereka, 1) menggunakan pilihan metode yang eklektik, 2) menggunakan aktivitas yang berdimensi kreatif, 3) mengajar dengan cara yang fleksibel atau menyesuaikan dan memodifikasi pengajaran pada saat pembelajaran, 4) mencari cara-cara baru dalam melakukan sesuatu, 5) mengadaptasi pembelajaran, 6) menggunakan teknologi, dan 7) mencari cara-cara kreatif untuk memotivasi siswa. Hasilnya, seluruh guru menerapkan ketujuh aspek tersebut dalam proses belajar mengajar. Dan ada 3 faktor mengapa guru bahasa Inggris merancang materi pembelajaran bahasa Inggris yang kreatif, 1) materi pembelajaran dikontekstualisasikan, 2) materi pembelajaran dirancang sesuai kebutuhan siswa, dan 3) personalisasi. Setelah menganalisis data, dapat diputuskan bahwa semua guru memiliki ketiga faktor tersebut dalam merancang materi pembelajaran bahasa Inggris yang kreatif. Pendidikan Profesi Guru Prajabatan (PPG) cukup kreatif dalam merancang bahan ajar.Kata Kunci: Kreativitas guru; materi ajar kreatif; pendidikan profesi guru; PPG